2012
DOI: 10.1590/s0482-50042012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Frequência elevada de calcinose em dermatomiosite juvenil: estudo de fatores de risco

Abstract: Objective: To assess the frequency of calcinosis in patients with juvenile dermatomyositis, and the possible risk factors for that manifestation. Methods: Medical record review of 34 patients, with an emphasis on the following characteristics: demographic, clinical and laboratory data; type of treatment; adherence to treatment; disease course (monocyclic, chronic and polycyclic); and disease severity. Patients were divided into two groups as follows: those who developed calcinosis (up to the sixth month of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It was also related to disease control, chronicity and the presence severe skin involvement [13]. However in a study of 34 cases of JDM, no risk factors for calcinosis were found [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was also related to disease control, chronicity and the presence severe skin involvement [13]. However in a study of 34 cases of JDM, no risk factors for calcinosis were found [1].…”
Section: Discussionmentioning
confidence: 99%
“…Calcinosis, a well-recognized sequela, is considered one of the features by which JDM differs from adult dermatomyositis as it generally occurs in 10% -70% of children with JDM [1]. Although it is not one of the diagnostic criteria, its progression may contributes to increased morbidity [8] and even mortality in JDM patients as it may continue even if the disease was controlled [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations